2020
DOI: 10.1155/2020/5281251
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Angiopoietin-Like Protein 4 Levels in Serum or Urine Correlate with Different Biochemical Markers in Hyperlipidemia-Related Proteinuria

Abstract: Angiopoietin-like protein 4 (ANGPTL4) is widely known as a key regulator of lipid metabolism. We investigated the relationship between ANGPTL4 expression in serum or urine and blood lipid or urine protein levels of patients with hyperlipidemia- (HL-) related proteinuria. Sixty-eight patients with HL-related proteinuria (HL-Pro group), 68 patients with HL without proteinuria (HL-NPro group), 46 patients with non-HL-related proteinuria (NHL-Pro group), and 50 healthy control (Con) subjects were selected. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It was found that the ANGPTL4 E40K mutation was correlated with low plasma triglyceride levels [32]. Gao et al [33] found a positive correlation between serum ANGTL4 and triglyceride only in patients with hyperlipidemia; no correlation was found in non‐hyperlipidemia patients. In our study, we indicated that there was no correlation between serum ANGPTL4 and triglyceride in MCD or MN patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the ANGPTL4 E40K mutation was correlated with low plasma triglyceride levels [32]. Gao et al [33] found a positive correlation between serum ANGTL4 and triglyceride only in patients with hyperlipidemia; no correlation was found in non‐hyperlipidemia patients. In our study, we indicated that there was no correlation between serum ANGPTL4 and triglyceride in MCD or MN patients.…”
Section: Discussionmentioning
confidence: 99%